Effects of fibroblast growth factor 21 on the heart - Pongpan Tanajak (2018)
© 2015 Society for Endocrinology. Fibroblast growth factor 21 (FGF21) is a novel polypeptide ligand that has been shown to be involved in several physiological and pathological processes including regulation of glucose and lipids as well as reduction of arteriosclerotic plaque formation in the great vessels. It has also been shown to exert cardioprotective effects in myocardial infarction, cardiac ischemiareperfusion injury, cardiac hypertrophy and diabetic cardiomyopathy. Moreover, FGF21 protects the myocardium and great arteries by attenuating remodeling, inflammation, oxidative stress and also promoting the energy supply to the heart through fatty acid b-oxidation. This growing evidence emphasizes the important roles of FGF21 in cardioprotection. This review comprehensively summarizes and discusses the consistent and inconsistent findings regarding the beneficial effects of FGF21 on the heart available from both basic research and clinical reports. The details of the signaling, biological and pharmacological effects of FGF21 with regard to its protection of the heart are also presented and discussed in this review.